Relevance of Esp Syllabus for Professional Courses- in Elt Context of Kerala - Nazir.P.K, Mohamed; Poonkodi, M (International Journal of Psychosocial Rehabilitation, 2020)
“We employ people who are capable; however, students with good academic records as well as language skills make a good asset to the company and may also be offered a better profile.”(Aspiring Mind).The current scenario of job market is explicit in the words of the HR of Syntel implying the dominance of English speaking proficiency for professional students to be ‘market ready’. This article is an attempt to analyse the existing English syllabus and study materials for professional courses contextualizing the need of the time for implementing ESP syllabus to meet their professional language requirements both in academic and professional domain. Study materials offered to the professional students in Polytechnic, Engineering, Nursing and Vocational Higher Secondary courses are analyzed in ESP perspective to bring out the causes for the poor performance in English communication skill of our professional students. The article suggests a model syllabus based on English for Specific Purpose (ESP) for professional courses in the state of Kerala. This study discusses the approaches in English teaching for professional courses including Polytechnic, Engineering, Nursing courses and Vocational Higher Secondary courses in the state of Kerala where the current English syllabus fails to meet the basic needs of the learners in developing English speaking skill. This study is of pivotal importance in pointing out the crucial role of English language proficiency for professional students.